Heterogeneous fate choice of genetically modulated adult neural stem cells in gray and white matter of the central nervous system. Issue 2 (21st October 2019) - Beyer, Felix; Jadasz, Janusz; Samper Agrelo, Iria; Schira‐Heinen, Jessica; Groh, Janos; Manousi, Anastasia; Bütermann, Christine; Estrada, Veronica; Reiche, Laura; Cantone, Martina; Vera, Julio; Viganò, Francesca; et al.
Abstract: Apart from dedicated oligodendroglial progenitor cells, adult neural stem cells (aNSCs) can also give rise to new oligodendrocytes in the adult central nervous system (CNS). This process mainly confers myelinating glial cell replacement in pathological situations and can hence contribute to glial heterogeneity. Our previous studies demonstrated that the p57kip2 gene encodes an intrinsic regulator of glial fate acquisition and we here investigated to what degree its modulation can affect stem cell‐dependent oligodendrogenesis in different CNS environments. We therefore transplanted p57kip2 knockdown aNSCs into white and gray matter (WM and GM) regions of the mouse brain, into uninjured spinal cords as well as in the vicinity of spinal cord injuries and evaluated integration and differentiation in vivo. Our experiments revealed that under healthy conditions intrinsic suppression of p57kip2 as well as WM localization promote differentiation toward myelinating oligodendrocytes at the expense of astrocyte generation. Moreover, p57kip2 knockdown conferred a strong benefit on cell survival augmenting net oligodendrocyte generation. In the vicinity of hemisectioned spinal cords, the gene knockdown led to a similar induction of oligodendroglial features; however, newly generated oligodendrocytes appeared to suffer more from the hostile environment. This study contributes to our understanding of mechanisms of adult oligodendrogenesis and glial heterogeneity and further reveals critical factors when considering aNSC mediated cell replacement in injury and disease. Main points: White and grey matter differentially regulate stem cell dependent oligodendrogenesis. A dominant positive impact is mediated via suppression of the p57kip2 gene. Lesion environment negatively affects new oligodendrocyte generation and survival.